Partisipasi Masyarakat Dalam Restorasi Hutan Mangrove(Studi Deskriptif Kualitatif Program Partisipasi Masyarakat Melalui Kelompok Tani Sidodadi Maju (KTSM) Desa Banggi Kecamatan Rembang Kabupaten Rembang) - Mudjab, Saiful, Agus Triyono, M.Si (2017)
Mangrove forests, or better known as the Jembatan Merah is the result of development undertaken Kelompok Tani Sidodadi Maju (KTSM) Banggi Desa Rembang. Pond farmer groups staffed by people from around the mangrove forests which mostly work as fishermen and fish farmers. Each member has the duties, rights and obligations within the group or mangrove forest tour. This study is a qualitative research that aims to determine how the community empowerment program through the restoration and conservation. Data collected by interview, observation and documentation. Informant interviews are Kelompok Tani Sidodadi Maju (KTSM), BLH (head of the environmental damage control and environmental conservation), and rural communities Banggi market. While the observation is made by taking pictures of objects in Mangrove Forest Mangrove Forest and operational activities. In addition, researchers also conducted studies KTSM library of documents as supporting data in this study. The results of this study indicate if the program implemented in empowering communities through the restoration and conservation of the Market Village Banggi include: planting of mangrove, mangrove tree nursery, maintenance, restoration, mangrove fruit processing, and the development of ecotourism. Keywords : Community development, restoration, mangrove forests.